Electrical Resistance and Magnetoresistance of Modified Carbon Nanotubes - T.A. Len; I.V. Ovsienko; L.Yu. Matzui; A.V. Tugay (Журнал нано- та електронної фізики)
The paper presents the results of the experimental studies of the magnetoresistance and electrical resistance of carbon nanotubes modified with iron and iron oxide. A comprehensive study of the processes, which act with change in the temperature of modified CNTs, is performed. Joint analysis of the structural studies and electrical transport characteristics is enabled to explain new and interesting results. It is established that modification with iron has little effect on the electrical resistance. On the other hand, modification is strongly reflected on the ferromagnetic resistance anisotropy. It is shown that the localization mechanism and anisotropic magnetoresistance are manifested in magnetoresistance. Anisotropic magnetoresistance arises due to the features of magnetization of ferromagnetic phase in an external magnetic field.